A Study Protocol for a Parallel-Designed Trial Evaluating the Impact of Plant-Based Diets in Comparison to Animal-Based Diets on Health Status and Prevention of Non-communicable Diseases—The Nutritional Evaluation (NuEva) Study - Dawczynski, Christine (Frontiers in Nutrition, 2021)
Background and aims Currently, there is a continuing upward trend for vegetarian and the vegan lifestyles in Germany and Europe. The implementation of vegetarian and vegan lifestyles is characterized by omitting defined food groups such as fish, meat, sausage (vegetarians), or dairy products and honey (ve-gans). This carries the risk of an undersupply of valuable nutrients. The NuEva study is designed to examine this hypothesis and to evaluate the impact of plant-based diets on health status and dis-ease risk. Methods The NuEva study is a parallel-designed trial with at least 55 participants for each diet (vegetarian, vegan, flexitarian [rare meat/sausage consumption, once or twice per week]), and participants who consume a traditional Western diet as the control group. In the screening period critical nutrients are identified for the studied diets by analysis of a broad spectrum of nutrients in the human samples (fatty acids, vitamins, minerals, trace elements, nutrient metabolites). Results Based on the data from the screening period, defined menu plans, ensuring an adequate nutrient intake in accordance with the nutritional guidelines are prepared for each group. The plans are adapted and personalized to individual energy requirements based on the basal metabolic rate and physical activity level. The compliance with the NuEva concept and their impact on nutrient status and cardiovascular risk factors are validated during the intervention period of the NuEva study over one year. To investigate the impact of the studied diets on the microbiome, feces samples are col-lected at the beginning and after the 12month intervention period (follow up: 12 months). Conclusion The NuEva study is designed to investigate the impact of common diets on health and disease sta-tus, with focus on prevention of cardiovascular diseases. In addition, the effectiveness of the pre-pared nutritional coaching strategy, ensuring optimal nutrient intake in accordance with the guide-lines, is validated during the intervention period of the NuEva study. Registered under ClinicalTrials.gov Identifier no. NCT03582020.